2013
DOI: 10.1021/am302893r
|View full text |Cite
|
Sign up to set email alerts
|

Methyl/Allyl Monolayer on Silicon: Efficient Surface Passivation for Silicon-Conjugated Polymer Hybrid Solar Cell

Abstract: We demonstrate a hybrid Schottky junction solar cell based on methyl/allyl groups terminated silicon nanowire arrays (SiNWs) and poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) with a power conversion efficiency (PCE) of 10.2%. The methyl/allyl organic monolayer on silicon can act as an excellent passivation layer for suppressing surface charge recombination, which is characterized by grazing angle attenuated total reflectance Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 33 publications
1
79
0
2
Order By: Relevance
“…The device without Liq layer displays the lowest value of 0.801 eV, while the device with 1-nm-thick Liq/Al exhibited a higher value (0.890 eV). Accordingly, the V oc of the device with Al as rear electrode is 0.560 V, which is comparable to the device based on methyl terminated planar Si, [ 22 ] and the V oc of the device with 1 nm Liq/Al as rear electrode reaches 0.609 V. It is worth noting that the value of 0.609 V is comparable with highly engineered Si solar cells with diffused p-n junctions, which typically exhibit V oc of 0.6-0.7 V. [ 23 ] To the best of our knowledge, it is the highest V oc ever reported for hybrid solar cells based on Si and PEDOT:PSS.…”
Section: Doi: 101002/aenm201300923mentioning
confidence: 53%
“…The device without Liq layer displays the lowest value of 0.801 eV, while the device with 1-nm-thick Liq/Al exhibited a higher value (0.890 eV). Accordingly, the V oc of the device with Al as rear electrode is 0.560 V, which is comparable to the device based on methyl terminated planar Si, [ 22 ] and the V oc of the device with 1 nm Liq/Al as rear electrode reaches 0.609 V. It is worth noting that the value of 0.609 V is comparable with highly engineered Si solar cells with diffused p-n junctions, which typically exhibit V oc of 0.6-0.7 V. [ 23 ] To the best of our knowledge, it is the highest V oc ever reported for hybrid solar cells based on Si and PEDOT:PSS.…”
Section: Doi: 101002/aenm201300923mentioning
confidence: 53%
“…[1][2] The reactivity of hydrogen-terminated Si(111) (H-Si(111)) surfaces toward organic nucleophiles, including alkenes, [3][4] alkynes, [5][6] amines, [7][8][9][10][11] thiols and disulfides, [12][13] Grignards, [14][15] and alcohols, [16][17][18][19][20][21][22][23][24][25] has been widely exploited to impart desirable functionality to the Si interface. These surface reactions have been used to control the interface between Si and metals, [26][27][28][29][30][31] metal oxides, [32][33][34][35] polymers, [36][37][38][39][40][41] and redox assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the predominant Si chemical state at the surface is S coordinated Si which has a potential to eliminate surface dangling bonds and strained dimer bonds at the Si (100) surface [29]. Zhang et al [31] suggested that the Si surface termination state plays a key role on the electrical output of the Sibased devices. As compared to a CZTS/as-cleaned n-Si diode, the number of charge traps in Si near the CZTS/Si interfaces is significantly decreased for CZTS/sulfidetreated n-Si diodes.…”
Section: Resultsmentioning
confidence: 99%